International Conference on Networking and Services (ICNS '07) 2007
DOI: 10.1109/icns.2007.35
|View full text |Cite
|
Sign up to set email alerts
|

Ant Routing in Mobile Ad Hoc Networks

Abstract: We study the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Switched ACO based MP-DSR (SAMP-DSR) [8] is based on Multi-Path Dynamic Source Routing introduced in [9] and Enhanced Multi-path Dynamic Source Routing (EM P-DSR) algorithm proposed in [10], which uses ants pro-actively to feed its re -active path discovery process with global data. The approach presented in [8] is a QoS-aware routing protocol, considering end-to-end reliability parameter as a constraint while t rying to minimize other parameters such as delay.…”
Section: Samp-dsrmentioning
confidence: 99%
“…Switched ACO based MP-DSR (SAMP-DSR) [8] is based on Multi-Path Dynamic Source Routing introduced in [9] and Enhanced Multi-path Dynamic Source Routing (EM P-DSR) algorithm proposed in [10], which uses ants pro-actively to feed its re -active path discovery process with global data. The approach presented in [8] is a QoS-aware routing protocol, considering end-to-end reliability parameter as a constraint while t rying to minimize other parameters such as delay.…”
Section: Samp-dsrmentioning
confidence: 99%
“…Coal production technology database is responsible to store and manage the production technology information, which generated in mine design and production process mainly including geological data which signifies the geological relationship, the device information from mine production, production design information from the 179 production process and Real-time monitoring test data during production and so on [7,8]. The data is the basis of achieve a virtual 3D geological modeling and mine, which all require to store in a database by a variety of file formats, coal mine database system structure shown in Fig.3.…”
Section: Figure 2 Evolution Of Database Information Flowmentioning
confidence: 99%
“…Systems vary among others in terms of formulas used for pheromone updates, cost functions (hop-count, delay, or some measure of link quality including signalto-noise ratio, congestion or packet loss ratio, or any combination of those) and mechanisms used to improve the performance. Studies such as [3,9] have shown that directly applying ant-based systems developed for wired networks such as AntNet results in lower performance compared to conventional MANETs protocols, and in particular to AODV [21], which is used as the reference protocols in most of the studies. In the following, the focus is on the mechanisms introduced specifically to address the challenges listed in Section 2.2.…”
Section: Solutionsmentioning
confidence: 99%